Simulation of two-phase flow on shell side of VVER-440 secondary boilers - Gergely, K.; Gabor, S.; Tamas, R. (Надійність і довговічність машин і споруд, 2009)
Shell side flow in VVER-440 steam generators has been simulated by using twodimensional and three-dimensional geometrical approach. A number of operating states have been analyzed: nominal and increased power load with the original feed water injection (within the tube bank) and with presently used water injection (above the tube bank). The mathematical model involves physical effects such as: thermal expansion of water phase, local condensation in the region of feed water injection (mixed pre/heater tank), variable slip velocity of the bubbly phase depending on local volume fraction of steam, spatial variation of the water level above the tube bank settling of disperse corrosion product under the tube bank. Micro-models have been developed for calculation of anisotropic resistance of the tube bank and pipe supports, local heat flux over the tube surfaces and the spatial variation of water injection intensity. Water surface elevation and disperse phase deposition patterns are in line with measured data published in scientific literature.